Synthesis of Organic Semiconductor Nanoparticles with Different Conformations Using the Nanoprecipitation Method - Yoshioka, Nathalia A.; Faraco, Thales A.; Barud, Hernane S.; Ribeiro, Sidney J. L. [UNESP]; Cremona, Marco; Fragneaud, Benjamin; Maciel, Indhira O.; Quirino, Welber G.; Legnani, Cristiano (MDPI, 2022)
In recent years, nanoparticulate materials have aroused interest in the field of organic electronics due to their high versatility which increases the efficiency of devices. In this work, four different stable conformations based on the organic semiconductors P3HT and PC71BM were synthesized using the nanoprecipitation method, including blend and core-shell nanoparticles. All nanoparticles were obtained free of surfactants and in aqueous suspensions following the line of ecologically correct routes. The structural and optoelectronic properties of the nanoparticles were investigated by dynamic light scattering (DLS), transmission electron microscopy (TEM), scanning electron microscopy (SEM), UV-visible absorption spectroscopy and UV-visible photoluminescence (PL). Even in aqueous media, the blend and core-shell nanoparticles exhibited a greater light absorption capacity, and these conformations proved to be effective in the process of dissociation of excitons that occurs at the P3HT donor/PC71BM acceptor interface. With all these characteristics and allied to the fact that the nanoparticles are surfactant-free aqueous suspensions, this work paves the way for the use of these colloids as a photoactive layer of organic photovoltaic devices that interface with biological systems.
Keywords: aqueous suspensions; nanoprecipitation method; organic semiconductor nanoparticles; P3HT; PC71BM